The understanding of the Islamic community's intention toward religious tourism - Mu'ammar, Zuhdi; Sudarsono, Heri; Rahmi, Asri Noer; Hawariyuni, Weni (Faculty of Business & Economics, Universitas Islam Indonesia, 2023)
Purpose – This study aims to analyze the influence of attitudes, subjective norms, perceived behavioral control, service quality, and religious tourism literacy on people's intention in recommending and returning to religious tourism destinations.Research methods – The data source for this research was a survey method with a questionnaire distributed via broadcast on social media. This research uses a quantitative data processing method using structural equation modeling partial least squares (SEM-PLS) analysis with the SmartPLS 3.3 statistical tool.Findings – The results of this study show that subjective norms (SN), attitudes (ATT), and religious tourism literacy (RTL) have a significant influence on the intention to recommend and revisit religious tourism. Meanwhile, service quality (SQ) and perceived behavioral control (PBC) were not accepted and did not have a significant effect on the intention to recommend and revisit religious tourism.Implications – The government can also focus on developing religious tourism literacy programs to increase public knowledge, which, in turn, can enhance interest, positive attitudes, and the intention to recommend and revisit. Considering these implications, destination managers and stakeholders can design more effective strategies to enhance attractiveness and visitor satisfaction and contribute to the sustainable development of religious tourism.Originality – This model adopts the Theory of Planned Behavior (TPB) by incorporating service quality and religious tourism literacy. Service quality and religious tourism literacy are considered appropriate factors to capture issues related to the community's intention to recommend and revisit religious tourism destinations